2018
DOI: 10.1007/s00417-018-4053-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of segmentation errors and motion artifacts in OCT-angiography differ among retinal diseases

Abstract: Prior to both qualitative and quantitative analysis, OCT-A images must be carefully reviewed as motion artifacts and segmentation errors in current OCT-A technology are frequent particularly in pathologically altered maculae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 35 publications
1
70
2
4
Order By: Relevance
“…Our inter-observer agreement is similar to that reported by Munk et al 16 (κ =0.52) for superficial capillary plexus on the Optovue device. Lauermann et al 17 reported 89% agreement in their MAS and SAS grading between two graders, whereas we had only 74.5% agreement between the three graders and 67%-83% agreement between two graders (Tables S1-S3).…”
Section: F I G U R E 3 Receiver Operating Characteristic Curves Showicontrasting
confidence: 55%
See 3 more Smart Citations
“…Our inter-observer agreement is similar to that reported by Munk et al 16 (κ =0.52) for superficial capillary plexus on the Optovue device. Lauermann et al 17 reported 89% agreement in their MAS and SAS grading between two graders, whereas we had only 74.5% agreement between the three graders and 67%-83% agreement between two graders (Tables S1-S3).…”
Section: F I G U R E 3 Receiver Operating Characteristic Curves Showicontrasting
confidence: 55%
“…Therefore, clinical trials of retinal vascular disease that examine OCTA parameters as secondary endpoints need to anticipate high rates (60%‐70%) of failure to acquire acceptable image for quantitative analysis. A previous study suggested that poor visual acuity and unstable fixation contribute to motion artefact and segmentation error . We showed that among patient factors (age and sex) and ocular factors (visual acuity, eye pathology and macular status) decreased visual acuity was the only significant predictor for unacceptable OCTA image quality.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Only OCTA scans with a signal strength ≥7, centred on the fovea, and the absence of motion as well as projection artefacts were considered (Lauermann et al. 2018b; Spaide et al. ).…”
Section: Methodsmentioning
confidence: 99%